Economic Development through Social Entrepreneurship: Case Study of Rural Innovation Hubs in Balikpapan - Amirul Mukmin Iskandari (Generasi Sains Indonesia, 2025)
Social entrepreneurship has emerged as an alternative pathway to foster economic development while addressing social challenges in marginalized communities. One institutional model that embodies this approach is the rural innovation hub, which provides training, networking, and market access to empower local entrepreneurs. This study examines the role of rural innovation hubs in Balikpapan, Indonesia, in promoting inclusive economic growth. Using a mixed methods case study design, data were collected from 180 respondents across three hubs operating in agriculture, handicrafts, and digital services. Quantitative findings show that participation in hub programs leads to significant improvements in household income, with average increases exceeding 50 percent. Digital service enterprises recorded the highest growth, reflecting sector-specific advantages in capturing emerging market opportunities. Qualitative evidence further highlights the hubs’ effectiveness in providing access to markets, entrepreneurial skills development, and networking opportunities, although challenges in accessing affordable capital remain persistent. The study also reveals strong participation from women and young entrepreneurs, underscoring the inclusivity of the hub model and its contribution to gender equity and youth empowerment. These findings suggest that rural innovation hubs in Balikpapan not only enhance local livelihoods but also foster social value creation by building community resilience. Nevertheless, limitations in financial access point to the need for stronger policy support and partnerships with financial institutions to ensure sustainability. Overall, the Balikpapan case demonstrates the potential of rural innovation hubs as platforms for advancing social entrepreneurship and sustainable economic transformation in developing regions.